Different approaches in sulfonated poly (ether ether ketone) conductivity measurements - Fedorenko, D.; Vaivars, Guntars (Institute of Physics Publishing, 2019)
Ion conductivity of sulfonated poly (ether ether ketone) (SPEEK) membranes with various degree of sulfonation (DS) was investigated using impedance analysis with different measuring cell configuration and ion conductivity was calculated from resistances of polymer membranes. SPEEK was synthesized from poly (ether ether ketone) (PEEK) via sulfonation reaction in concentrated sulfuric acid (95-98%). Scanning electron microscopy (SEM) analysis of membrane surface was performed to determine possible mechanical damage to the membrane during resistance measurements.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics